Bardo : interval of possibility - Khenpo Karthar Rinpoche (New York : KTD Publications, 2007)
Khenpo Karthar Rinpoche gives an exceptionally clear and lucid explanation of Aspiration for the Bardo, graciously giving the necessary time and attention to its more obscure points. His commentary, however, is not merely a bare description of the sequence of events in the process of dying and death, but is underscored throughout with the purpose and urgency of aspiration. We are clearly instructed on what to practice and how to train ourselves at every point of opportunity, "whether in the waking state or the dream state" and even within the interval experience itself.
Includes index.
Keywords: The First Part; The Middle Part; The Last Part